The perfect pet - Palatini, Margie; Whatley, Bruce ([New York] : HarperCollinsPublishers, 2003)
After Elizabeth's parents do not agree with her various suggestions for the perfect pet, she discovers a solution.
School Library Journal
Horn Book
Bulletin (Center for Children's books)
School Library Journal.
Horn Book.
Bulletin (Center for Children's books).
Keywords: Pets -- Juvenile fiction; Insects -- Juvenile fiction; Pets -- Fiction; Insects -- Fiction; Pets -- Fiction; Insects -- Fiction